Cathartic Paths of the Gothic in Ciemno, prawie noc by Joanna Bator - Łowczanin, Agnieszka (Text Matters: A Journal of Literature, Theory and Culture, 2024)
The aim of this paper is to investigate how the Gothic is employed in Joanna Bator’s novel Ciemno, prawie noc [Dark, Almost Night]. I frame my analysis on the author’s assertion that “Poland is a horror,” exploring firstly how the Gothic serves as an aesthetic framework that intertwines different time periods and family histories within the narrative. Secondly, I examine its role in grounding these temporal layers within the specific geographical location of Wałbrzych, which itself assumes a villain-like presence in the novel. I argue that Bator adapts the Gothic tradition for cathartic purposes, particularly in narrating transgenerational traumas. This approach enables the expression and understanding of a fractured past, potentially fostering a process of healing.